The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/ijc.30701
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of DAB2IP promotes colorectal cancer invasion and metastasis by translocating hnRNPK into nucleus to enhance the transcription of MMP2

Abstract: DOC-2/DAB2 interacting protein (DAB2IP) is a RasGAP protein that shows a suppressive effect on cancer progression. Our previous study showed the involvement of transcription regulation of DAB2IP in metastasis of colorectal cancer (CRC). However, the molecular mechanisms of DAB2IP in regulating the progression of CRC need to be further explored. Here, we identified heterogeneous nuclear ribonucleoprotein K (hnRNPK) and matrix metalloproteinase 2 (MMP2) as vital downstream targets of DAB2IP in CRC cells by two-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 39 publications
(98 reference statements)
1
25
0
Order By: Relevance
“…Considering that DAB2IP plays a critical role in regulating the activation of ERK1/2 pathway in colorectal cancer [ 13 , 31 ] and activation of ERK1/2 signaling pathway contributes to tumor cell growth and metastasis [ 21 23 ], we asked whether DAB2IP modulates the growth and metastasis of gastric cancer cells via regulating ERK1/2 signaling pathway. In accordance with other studies [ 13 , 31 ], blockade of DAB2IP enhanced the phosphorylation of ERK1/2 in gastric cancer cells ( Figure 5(a) ) and the enhanced proliferation and migration ability induced by DAB2IP knockdown was remarkably reduced after incubation with U0126 in SGC7901 gastric cancer cells (Figures 5(c) and 5(d) ). Furthermore, EMT induced by DAB2IP knockdown was reversed after treatment with U0126 in both AGS and SGC7901 gastric cancer cells ( Figure 5(b) ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that DAB2IP plays a critical role in regulating the activation of ERK1/2 pathway in colorectal cancer [ 13 , 31 ] and activation of ERK1/2 signaling pathway contributes to tumor cell growth and metastasis [ 21 23 ], we asked whether DAB2IP modulates the growth and metastasis of gastric cancer cells via regulating ERK1/2 signaling pathway. In accordance with other studies [ 13 , 31 ], blockade of DAB2IP enhanced the phosphorylation of ERK1/2 in gastric cancer cells ( Figure 5(a) ) and the enhanced proliferation and migration ability induced by DAB2IP knockdown was remarkably reduced after incubation with U0126 in SGC7901 gastric cancer cells (Figures 5(c) and 5(d) ). Furthermore, EMT induced by DAB2IP knockdown was reversed after treatment with U0126 in both AGS and SGC7901 gastric cancer cells ( Figure 5(b) ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, no association between variant in rs7025486 and the incidence of CAD was observed, while the GWAS and replicating study consistently found the effects of a common variant in DAB2IP (rs7025486) on the development of CAD and other complications [ 12 , 26 , 27 ]. In cancer cells, DAB2IP, as a Ras-GTPase, exerted a suppressive effect on tumor invasion and maintained chromosomal stability [ 13 , 14 , 28 ]. However, the molecular mechanisms of DAB2IP in regulating the progression of atherosclerosis need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…As aged cells are downregulated in their expression of collagen IV [ 83 ], this may lead to more efficient BM degradation in the aged host. Additionally, in many cancers, Dab2 downregulation leads to increased transcription of the ribonucleoprotein hnRNPK, which then enhances MMP2 transcription by the metastatic cells [ 91 ]. Thus, downregulation of Dab2, as observed in OvCa metastatic cell lines, may be correlated with increased MMP2 expression.…”
Section: Aging Modifies the Metastatic Microenvironmentmentioning
confidence: 99%